Analisis Kinerja Keuangan Perusahaan Sebelum Dan Sesudah Akuisisi: Studi Kasus pada Akuisisi PT Garudafood Putra-putri jaya Tbk terhadap PT Mulia Boga Raya Tbk - Dewi Dersanala; Risma Indah Islami; Harviyani Azzahra; Endang Kartini Panggiarti (International Forum of Researchers and Lecturers, 2025)
Financial performance is a description of a company's activities. Good financial performance can reflect the health conditions of good financial governance as well. The aim of this research is to analyze how the acquisition affects financial performance before and after the acquisition. The subject of this research used the acquiring companies PT Garuda Food Tbk and PT Mulia Boga Raya Tbk in the 2017-2022 period by examining the financial performance three years before and three years after the acquisition. This research is a type of comparative research, which means comparing financial performance between before and after the acquisition. The analysis in this research is measured using four financial ratios, namely Return On Assets (ROA), Return On Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER). Based on the results of the analysis, it shows that there are significant differences in total ROA, ROE, CR and DER between before and after acquisition